Smart home: Pintu Otomatis Berbasis Voice Recognition - Jefiza, Adlian; Puspita, Widya Rika; Firdaus, Fadli; Sihombing, Fitri Andini; Setiawan, Afif; Herlina, Gise; Milala, Gerry Ibnu Luthfi Sembiring; Fernanda, Heri (JURNAL INTEGRASI, 2024)
The current development of the Smart home is not only used for automation and monitoring of a room, but also used as security or what is usually called security. One form of smart home security technology is an automatic door lock installed in one of the laboratories at the Batam State Polytechnic. Automatic door lock devices are created using Voice Recognition as command input. Users can give the word Open to unlock the door and Close to lock the door. Selenoid Door Lock is used as a tool to lock doors, and LEDs and speakers are used for information. The tool is tested by giving commands by registered and unregistered users. The test results were 100% of the tool worked for registered users with normal Voice intonation, 77% of the tool worked for unregistered users with normal Voice intonation, 48% of the tool worked for registered users with abnormal Voice intonation and 43% of the tool worked for registered users. not registered with abnormal Voice intonation. Thus, the average tool works well by 67%.